Design and implementation of an innovative canned cycle for variable pitch thread cutting on CNC milling machines - Omirou, Sotiris L.; Chasos, Charalambos A. (International journal of advanced manufacturing technology, 2024)
This paper presents the development of a new canned cycle for CNC milling machines capable of cutting threads with variable pitch, addressing a significant limitation in modern CNC systems. While existing CNC milling machines provide canned cycles for thread cutting, they lack the capability to program variable pitch, necessitating reliance on CAM systems. In response, the proposed canned cycle offers increased flexibility, quicker setup times, and reduced dependence on CAM systems. The cycle accommodates both internal and external threads, supports left-hand or right-hand threading, and incorporates a user-friendly control panel for easy programming. To validate its efficiency, the canned cycle is implemented using a G-code parametric algorithm, and a series of simulation tests are conducted. The results demonstrate the viability and advantages of the new CNC milling feature in cutting threads with variable pitch, opening up possibilities for various mechanical applications.